Stilìstičnenavantažennâ folʹklornih epìtetìv u poezìï Borisa Olìjnika - Klìŝun, Galina; Čornenʹkij, Âroslav (Stylistyka, 1998)
The fundamental bulk of folklore epithets in B.Oliynyk’s poetry - are the constant epithets in semantic-emotional author’s interpretation, which functionate in poetry-parables and connected with historical themes, in intimate lyric poetry, and seldom in social-political and philosophical lyrics. In the basis of renovation figurativeness of folklore epithets in B.Oliynyk’s works are their combination with other lexical units; combination range is very wide: from changing ofthe traditional words in set expressions to close to sense or associatively connected with it-to join the folk-lore epithet with antonym of the main word of the traditional wordcombination. In combination they form metaphorical and symbolic meanings. The context is promoted to figurativeness renovation where the traditional folklore epithets are realizes in „unusual conditions”. In B.Oliynyk’s poetry folk-lore epithets are combinated in integral whole with other folk-lore elements-metaphors, comparisons and other popular poetry sym[1]bols, which favourthe formation ofthe corresponding sentiments ofthe reader.